Tectonic keratoplasty using small incision lenticule extraction-extracted intrastromal lenticule for corneal lesions. Issue 1 (January 2020) - Pant, Om Prakash; Hao, Ji-long; Zhou, Dan-dan; Pant, Manju; Lu, Cheng-wei
Objective: This study investigated an alternative approach for obtaining donor corneas for keratoplasty that can be used in nations with high corneal demand and high costs for treatment of non-healing ulcers or lesions. Methods: Eighteen patients (18 eyes) who underwent tectonic keratoplasty using small incision refractive lenticule extraction (SMILE)-extracted lenticule were included. Data were recorded regarding age, corneal status, corneal lesion location and size, preoperative and postoperative visual acuity, lenticule layer, and additional medical history. Results: Corneal thinning and corneal perforation in 13 and 5 patients, respectively, were treated with tectonic keratoplasty using SMILE-extracted lenticule. After tectonic keratoplasty, globe integrity was maintained in 16 of the 18 patients. The mean decimal visual acuity improved from 0.2555±0.3326 preoperatively to 0.3303±0.3487 at the final follow-up. Visual acuity improvement was greater in patients with corneal perforation than in patients with corneal thinning. In addition, visual acuity was most improved in patients with infratemporal lesions. Conclusion: Tectonic keratoplasty using SMILE-extracted lenticule is a comparatively safe, effective, and reliable alternative approach for the treatment of corneal lesions.